(untitled) (Historia, 2021)
In the period 1903-24 the Vaal River underwent a decisive process of change. After the founding of the Rand Water Board (1903) plans were implemented for the establishment of a water scheme for the Witwatersrand. In the article an explanation is offered on how industrial and urban development increased the demand for water. By the time the construction of the Barrage (1916-23) was completed a new era dawned for people along the river